2013
DOI: 10.4103/2230-8210.117231
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent parathyroid carcinoma and adenoma: A rare presentation of a rarer disease entity

Abstract: Parathyroid carcinoma is a rare disease. But multiglandular parathyroid neoplasm is even rarer. A high level of suspicion, on the basis of clinical, hematological tests and intraoperative findings is necessary to treat this disease entity, particularly in the absence of palpable neck masses. Preoperative localization is important. Bilateral neck exploration should be done routinely and all 4 glands seen to avoid missing out other pathological glands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 9 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…Functional PTCa occurrence is well documented, however, its sporadic synchronous occurrence in the presence of PTa in individuals with no identifiable risk factors has rarely been published. To our knowledge, only three (7,11,12) clearly documented cases have been previously reported (Table 1), with one case of nonfunctioning PTCa and PTa (13).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Functional PTCa occurrence is well documented, however, its sporadic synchronous occurrence in the presence of PTa in individuals with no identifiable risk factors has rarely been published. To our knowledge, only three (7,11,12) clearly documented cases have been previously reported (Table 1), with one case of nonfunctioning PTCa and PTa (13).…”
Section: Discussionmentioning
confidence: 95%
“…Hence, although PTCa is an uncommon cause of primary hyperparathyroidism, it is important to suspect and exclude it. Routine bilateral neck exploration with identification of all four parathyroid glands should be performed in individuals with suspected PTCa to minimise this risk (12).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only four patients with multiglandular concurrent parathyroid adenoma and carcinoma have been reported until now [9][10][11][12]. Chatterjee et al [9] have reported a case of multiglandular parathyroid neoplasm with carcinoma on one side and adenoma on the contralateral side of the neck. Goldfarb et al [12] have reported a patient with synchronous parathyroid carcinoma, parathyroid adenoma, and papillary thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 98%
“…Most of patients with parathyroid carcinoma present with a neck mass and these patients generally tended to have severe PHP [2] and absence of this findings result in significant diagnostic challenge for the clinician [9]. To our knowledge, until now only 9 PHP patients with large mediastinal ectopic parathyroid carcinoma have been reported in the literature [3][4][5][6][7][8] and four cases of concurrent parathyroid adenoma and carcinoma in the neck have been reported [9][10][11][12]. In this paper, a patient with concurrent ectopic mediastinal parathyroid carcinoma and neck parathyroid adenoma is presented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation